(untitled) (Research, Society and Development, 2021)
The laboratory diagnosis of ascariasis is done through the Parasitological Examination of Feces (EPF), which investigates the presence of Ascaris lumbricoides eggs in the feces. The Hoffman Method is based on spontaneous sedimentation and allows the concentration of eggs, cysts, oocysts and larvae of numerous species through gravitational sedimentation of a fecal sample. And the Direct Fresh Examination allows the identification of protozoa (trophozoites and cysts) and helminths (eggs, larvae and small adults). Objective: To compare the sensitivity of direct-fresh and Hoffman laboratory methods in the field of Parasitology. Methodology: The search for scientific articles was performed in electronic databases: Scientific Electronic Library Online (SCIELO), Latin American Literature on Health Sciences (LILACS), National Library of Medicine and the National Institute of Health (Pubmed). Publications from 2015 to 2021, in Portuguese, Spanish and English. Results and Discussion: Direct fresh examination and the technique of Hoffman, Pons and Janer or Lutz (HPJL) are the most used laboratory methods, as these techniques have as main advantage the minimal need for materials and financial resources. However, the disadvantage is that there is a large amount of fecal debris in the sediment, making preparation and microscopic examination difficult. Final Considerations: Fresh Direct and Hofmman, when used together, increase the probability of real and reliable diagnoses, especially in the diagnosis of helminth eggs and cysts, but separated, each has greater sensitivity in specific cases. Due to the scarcity of comparative studies of these two methods, it is evident and worth suggesting further research in this regard, since these methods are so important in the diagnosis of parasitic diseases, which have become a public health issue, but due to the difficult diagnosis it ends up being neglected in our day to day.